Promising Constructions of Sweet Cherry (Prunus avium L.) Orchards under Conditions of Ukrainian Forest-Steppe - Kishchak, Olena; Kishchak, Yuriy (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2019)
The purpose of the research was the comparative estimation of the modern sweet cherry (Prunus avium L.) orchards, created according to the foreign and domestic technologies with using the best large-fruited cultivars, high-productive rootstocks, modern methods of the pruning under the optimum dense trees distribution. Field, laboratory and comparative methods of the investigations were applied as well as statistical. The growth processes intensity in the orchards of cv. Regina on Gisela 5 appeared lower than on the middle rootstocks Gisela 6 and VSL-2. Among the pruning methods, the fan-trained crown proved averagely in the research years by 1.2–2.6 times less productive for all the explored cultivar-rootstock combinations as compared to the variants with the rounded small-size and multi-ax flattened crowns. High-productive constructions of the orchards with Talisman and Annushka varieties on the middle rootstocks VSL-2 were selected with a planting plan of 889 trees/ha and rounded small-size and multi-ax flattened crowns. At the age of six years those orchards provide the competitive yield level (8.1–12.5 t/ha) and fruits marketability (94.1–95.7 %). Comparison of the best domestic varieties such as Talisman and Annushka with Regina variety showed that they are competitive and not inferior of foreign ones not only in yield but also in marketable fruit quality. The largest fruits were found out in Talisman variety – 18.4 g with a diameter of 35 mm.The Regina orchards on Gisela 5 and Gisela 6 were low-productive and did not ensure the necessary production marketability level comparing with the Ukrainian orchards.